Finding one's own space in cyberspace. - BRUCKMAN, Amy (1996)
Explains that the Internet is made up of hundreds of thousands of separate communities, each with its own special character, and users have to employ a variety of techniques to choose those sites with which they would be comfortable. Advises the creation of a new newsgroup if a suitable online environment is not found.